Krankheit und Kultur Einführung in die kulturvergleichende Psychiatrie - Stompe, Thomas; Ritter, Kristina M. (MWV Medizinisch Wissenschaftliche Verlagsgesellschaft, 2014)
The first volume of the new Viennese series on transcultural psychiatry deals with the complex interaction of illness and culture, the central research field of cross-cultural psychiatry. It examines the influence of culture and society on the existence and frequency, the course and form of mental disorders as well as the concepts of illness and treatment in different cultures. The book broadens the view of mental disorders and critically questions our usual assumptions about normality. It comprehensively shows the interplay between illness and culture for the most important psychiatric disorders, such as anxiety disorders, schizophrenia, depression, delusion or personality disorders.